Ewolucja regulacji prawnej Prokuratorii Generalnej w Polsce na tle rozwiązań austriackich: [The evolution of the legal regulation of the State Treasury Solicitor’s Office in Poland against the Austrian solutions] (Studia Prawnicze / The Legal Studies, 2012)
Celem niniejszego artykułu jest prezentacja konstrukcji prawnej Prokuratorii Generalnej w Polsce na tle rozwiązań przyjętych w prawie austriackim, w którym jako jednym z pierwszych wprowadzono instytucję Prokuratury Finansowej, chroniącej interesy majątkowe państwa. Współczesna konstrukcja Prokuratury Finansowej Austrii oddziaływująca na rozwiązania w innych państwach, jest wynikiem ponad 200-letniego rozwoju tej instytucji i charakteryzuje się nowoczesnymi rozwiązaniami legislacyjnymi, zapewniającymi tej instytucji istotną rolę w życiu politycznym i gospodarczym państwa w sferze jego praw majątkowych. The structure of institutions, representing and defending state property in the course of civil law is important theoretical and practical, because it substantially determines the role of property in society and its impact on the functioning of the state in the economic sphere. The purpose of this article is to present the legal structure of State Treasury Solicitors’ Office, in Poland against the solutions adopted in Austrian law, which first introduced the institution of Financial Prosecutor, to protect the financial interests of the state. By comparing the structure of the State Treasury Solicitors’ Office with the objectives, tasks and functions of the Prosecutor Financial in Austria will be highlighted key features of the current institution in Poland. In comparison with the Austrian and Polish pre-war construction of the State Treasury Solicitors’ Office, the present institution is its narrow form. It only protects the rights and interests of the narrow sense (meaning) of the State Treasury, because due to subjective and objective limitations (e.g. it does not include inventoried state property or features that should meet to represent the interests of the state / advice, opinions, etc. /) defends the small part of rights and interests of the state.